Gender, Power, and Legal Injustice: A Feminist Legal Analysis of the Gendered Legal Persecution Through Salem Witch Trials in 1692-1693 - Chen, Liyu (Transactions on Social Science, Education and Humanities Research, 2025)
This essay seeks to explore the ways in which biased and gendered legal persecution manifested during the Salem Witch Trials. By examining the actions taken by the religious leaders and other members of the town, it becomes evident that legal persecution was used as a tool to confine women within their conventional gender roles. Throughout the 16th and 17th centuries, the label of “witch” was often applied to those who were marginalized or who failed to meet societal expectations, particularly independent women who did not adhere to patriarchal standards and rules. These women were seen as threats to the established social order. Using the harrowing experiences of the accused in the Salem Witch Trials, this paper attempts to explain how the trials were not just a series of legal proceedings, but a form of gendered legal persecution. It highlights how the trials were driven by a desire to maintain male dominance and suppress female autonomy, ultimately revealing the deep-seated sexism and fear that underpinned the events.